Investigating the use of copulas to improve the multi-objective optimisation cross-entropy method algorithm - Sayed, Atiyyah (Stellenbosch : Stellenbosch University, 2025)
Sayed, A. 2025. Investigating the use of Copulas to improve the Multi-Objective Optimisation Cross-Entropy Method algorithm. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d73a9204-f1a6-40e3-9947-53b38cbbafdf